Faktor-Faktor yang Mempengaruhi Kesuksesan Implementasi Sistem Informasi SDM di BPK RI - Citra Perwira (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
As a very valuable asset, human resource needs to keep improving the performance of human resource management (HRM) in organizations. For instance, by integrating information technology in automating HRM business process, which is known as the Human Resource Information System (HRIS). The embodiment of HRIS in Badan Pemeriksa Keuangan Republik Indonesia (BPK RI) is a web-based Sistem Informasi Sumber Daya Manusia (SISDM). The users’ acceptance level of SISDM is still low, meanwhile, it is a determinant factor of successful implementation of the information systems in several studies. Based on the conditions above, this study aims to analyse the factors that influence the successful implementation of SISDM at BPK RI. This study integrates the model of the Unified Theory of Acceptance and Usage of Technology (UTAUT) and the DeLone and McLean’s information systems success model. The population of this study was all the employees of BPK RI who have used the SISDM as the end-users. The sample was selected by using the simple random sampling technique. Data gathered from 255 respondents were analysed by using SmartPLS version 3 software. The results show that the successful implementation of SISDM is influenced by the usage intention and users’ satisfaction. The intention to use SISDM is affected by the performance expectancy, effort expectancy, social influence, system quality and users’ satisfaction. While the user satisfaction of SISDM is influenced by the information quality and system quality.